2016
DOI: 10.1080/21541248.2016.1173772
|View full text |Cite
|
Sign up to set email alerts
|

P-cadherin-mediated Rho GTPase regulation during collective cell migration

Abstract: This commentary addresses the role of P-cadherin in collective cell migration (CCM), a cooperative and coordinated migration mode, used by cells during normal and pathological migration processes. We discuss how cadherin-mediated cell-cell junctions (CCJs) play a critical role in CCM through their ability to regulate Rho GTPase-dependent pathways and how this leads to the generation and orientation of mechanical forces. We will also highlight the key function of P-cadherin (a poor prognostic marker in several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…As far as the cooperation of various cell types inside organoids is concerned, one can take into account the reorganization of adherens junctions and the force of transmission through them. It was demonstrated that remodeling of adherens junctions controls cell-cell cooperation during collective cell migration of MDCKII monolayers by the α-catenin-related mechanism (Matsuzawa et al 2018) and some studies point to the specific role of various cadherins, e.g., E-cadherin and P-cadherin, in collective cell movement in 3D (Plutoni et al 2016). Similarly, atypical Fat2 cadherin of Drosophila melanogaster is supposed to regulate collective cell movement during tissue rotation (Squarr et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As far as the cooperation of various cell types inside organoids is concerned, one can take into account the reorganization of adherens junctions and the force of transmission through them. It was demonstrated that remodeling of adherens junctions controls cell-cell cooperation during collective cell migration of MDCKII monolayers by the α-catenin-related mechanism (Matsuzawa et al 2018) and some studies point to the specific role of various cadherins, e.g., E-cadherin and P-cadherin, in collective cell movement in 3D (Plutoni et al 2016). Similarly, atypical Fat2 cadherin of Drosophila melanogaster is supposed to regulate collective cell movement during tissue rotation (Squarr et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we sought to investigate if the observed transdifferentiation of anillin-depleted MDA-MB-231 cells plays a causal role in inhibiting cell migration and invasion. We focused on cadherin overexpression since both E-and P-cadherins are known regulators of cell migration [52,53]. Either E-cadherin or P-cadherin were transiently downregulated in control and anillin-depleted MDA-MB-231 cells and effects of their depletion on cell motility were determined using the wound closure and Matrigel invasion assays.…”
Section: Downregulation Of E-cadherin Reverses Attenuated Migrating Amentioning
confidence: 99%
“…Given RHOU’s dual and opposing effects on the epidermis’ intercellular and cell-substratum borders, we were especially intrigued by the prominence in RHOU’s interactome of the p21-activated serine-threonine kinases, PAK1 and PAK2, and the guanine nucleotide exchange protein ARHGEF7 (β-PIX). These proteins are known to shuttle as a complex between adherens junctions, where tyrosine kinase receptor activity is silent and focal adhesions, where it is active (Livshits et al, 2012; Plutoni et al, 2016). Interestingly, EGFR was also present in our interactome (Supplementary file 6).…”
Section: Resultsmentioning
confidence: 99%